2012
DOI: 10.1038/sc.2012.53
|View full text |Cite
|
Sign up to set email alerts
|

Exercise participation barrier prevalence and association with exercise participation status in individuals with spinal cord injury

Abstract: Study design: Pass-code protected web survey. Objectives: Defining exercise participation barrier prevalence and association with exercise participation status in adults with spinal cord injury (SCI). Setting: World-wide web. Methods: Individuals Z18 years with ShCI in the United States completed a pass-code protected website survey (N ¼ 180). Odds ratios (OR) and OR 95% confidence interval (95% CI) assessed association between barrier presence and exercise participation. Results: No differences existed betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 9 publications
2
65
2
1
Order By: Relevance
“…These findings are consistent with those that have been reported previously with respect to regular physical activity among individuals who are newly discharged. 5 Although several studies in the chronic SCI population indicate internal barriers (for example, motivation) as a strong predictor of behaviour, 13 this was not reported in this study. Although we did not measure motivation or changes in the constructs of social cognitive theory as a result of our counselling intervention, the counselling support may have helped participants maintain interest in exercise.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…These findings are consistent with those that have been reported previously with respect to regular physical activity among individuals who are newly discharged. 5 Although several studies in the chronic SCI population indicate internal barriers (for example, motivation) as a strong predictor of behaviour, 13 this was not reported in this study. Although we did not measure motivation or changes in the constructs of social cognitive theory as a result of our counselling intervention, the counselling support may have helped participants maintain interest in exercise.…”
Section: Discussioncontrasting
confidence: 53%
“…12 Despite this, less than half of people with SCI report receiving any information about physical activity from their healthcare provider, and even fewer report receiving specific information about how and when to exercise. 13 Physicians are consistently recognized as an important source of LTPA information, 14 and specific preparation for LTPA during rehabilitation can serve as an important facilitator for continued participation. 5 In the cardiac rehabilitation model, the strength of physicians referral is the most significant predictor of long-term adherence, 15 and literature reviews suggest that patients are more likely to adhere to programs when they are referred, educated, and have a high amount of self-efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…As with other physical disabilities (Cowan et al, 2013;Martin Ginis et al, 2012;Mulligan et al, 2012;Saebu, 2010), the meta-synthesis revealed a lack of knowledge about where and how to exercise as a significant barrier to LTPA. When healthcare professionals were not unable to provide this information, people with SCI turned to their peers for advice and guidance on LTPA.…”
Section: Discussionmentioning
confidence: 92%
“…The high adherence rate in the PAG group can also be attributed to the fact that participation eliminated some of the most commonly reported barriers to exercise participation in the SCI population: knowledge about exercise, facility and equipment accessibility, and personal support. [18][19][20] This emphasizes the importance of not only allocating resources into the Physical activity guidelines and SCI CA Pelletier et al development of community-based exercise programs for people with SCI, but also stresses the value of personal support in order to encourage sustained and effective participation.…”
Section: Discussionmentioning
confidence: 99%